Strategic Interaction Between the Fiscal and Monetary Authorities Under Inflation Targeting - Kai Leitemo (Norges Bank, 2000)
This paper studies the strategic interaction between the fiscal and monetary authorities when the monetary policymaker pursues an underlying inflation target. Given that monetary policy is transparent and the fiscal policymaker can commit to a particular policy stance, the Stackelberg equilibrium can be implemented. If the conditions for Stackelberg leadership is not present, policies may end up in a Nash equilibrium, resulting in excessive interest and exchange rate volatility. Legislative restrictions on fiscal policy may then be stabilising, whereas they may be counterproductive in the Stackelberg case.
hdl:11250/2500399
Keywords: E61; E63; E42; E52; 330; small open economy; inflation targeting; policy coordination; policy interdependencies